Effectiveness of Multimedia and Education using Lecturing Method on Role of Vitamin D for Health Cadres - Sumartini Dewi; Adityana Sulistyo; Erwin Sumardi; Eka Puji Lestari; Kevin Sulay Wijaya; Paramitha Kusuma; Theresia Dewi; Agraini Agraini; Eldi Sauma; Winda Kurniati; Francisca Nungki Triandari; Shelly Iskandar; Tuti Kurnianingsih; Veranita Pandia (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To investigate the differences in the effectiveness of learning methods between multimedia and lecture methods on benefits of vitamin D for health from the perspective of health cadres' knowledge,. Methods: This study was an experimental study with a pre-and post-test design. The knowledge of health cadres was assessed using a questionnaire. The questionnaire was distributed before and after the health cadres received vitamin D education by two different methods. Data analysis was conducted using paired and independent t-test with a significance level of p <0.05. Results: A total of 59 health cadres participated in this study. Prior to education, the median test score for the multimedia group was 9.45, while the median test score for the lecture group was 82.70. After the education, the multimedia group and the lecture group got a median test score of 10.84. The multimedia method and lecture method significantly increased health cadres' knowledge with p-values of <0.02 and 0.003, respectively. There was no difference in the multimedia method's effectiveness compared to the lecture method in increasing the knowledge of health workers about vitamin D's role in health (p=0.62). Conclusion: The multimedia education method is as effective as the lecture method in increasing health cadres' knowledge about the role of vitamin D in health.